Soil quality trends across successive stages of post-coal mining reclamation - Arifin, Zainal; Bertham, Yudhi Harini; Wiryono, Wiryono; Putranto , Agus Martono H (Journal of Degraded and Mining Lands Management, 2025)
Soil Quality Index (SQI) assessment is a crucial parameter for evaluating the effectiveness of land reclamation objectives. This research aimed to analyze trends in soil quality changes across various stages of post-coal mining reclamation. This research was conducted in June 2024 at sites with varying soil ages at PT Inti Bara Perdana and in natural forest areas. This research employed descriptive-exploratory methods and involved open-field surveys. Sampling was conducted using purposive sampling at locations representative of the conditions at each site. Principal Component Analysis (PCA) was utilized to identify key indicators and determine the SQI. The results demonstrated that post-mining land reclamation significantly improved the physical, chemical, and biological quality of the soil. While the reclaimed soil quality has not yet fully reached the level of natural forest soil, the reclamation process exhibits strong potential for ecosystem recovery. SQI analysis revealed an increasing trend in soil quality as the reclamation age advanced. Linear variable analysis indicated a positive correlation between reclamation age and SQI development. Reclaimed areas aged 7 and 11 years exhibited SQI values exceeding 0.5, signifying successful reclamation and ecological sustainability.